PENGAWETAN SEBELAS JENIS KAYU DENGAN METODE RENDAMAN PANAS-DINGIN - Barly Barly; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
A study on the treatability of eleven wood species was carried out using hot and cold soaking treatment methods with Koppers Formula 7 as preservative. Specimens measuring 50 cm x 5 cm x 5 cm were soaked in five and ten percent preservative solution for a duration of one, two, and three hours and then allowed to cool while the timber is still soaked in the liquid. The penetration and retention were recorded. From this study the following conclusions could be drawn:The treatment schedule and concentration of solution have a highly significant effect on the preservative penetration and retention. Much higher retention was shown when longer hot soaking and higher concentration were employed.